2023
DOI: 10.7547/21-139
|View full text |Cite
|
Sign up to set email alerts
|

Postprocedural Opioid-Prescribing Practice in Nail Surgery

Abstract: Background: Ingrown toenails are a common condition requiring outpatient procedures in podiatric medical clinics. To prevent recurrence, chemical matrixectomy is often recommended. Postprocedural pain management is largely based on preferences rather than on a formal guideline. This study aims to explore the postprocedural prescribing behavior among practicing podiatric physicians to foster future guideline and policy development. Methods: We administered an open, voluntary, anonymous questionnaire via an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It remains up to the podiatric physician to assess their patients' opioid history, pain tolerance, and comorbidities to formulate a patient-centric and procedure-focused approach to determine which nonopioid analgesics and opioids are best for managing their patients' postoperative pain. [17][18][19][20] Financial Disclosure: None reported. Conflict of Interest: None reported.…”
mentioning
confidence: 99%
“…It remains up to the podiatric physician to assess their patients' opioid history, pain tolerance, and comorbidities to formulate a patient-centric and procedure-focused approach to determine which nonopioid analgesics and opioids are best for managing their patients' postoperative pain. [17][18][19][20] Financial Disclosure: None reported. Conflict of Interest: None reported.…”
mentioning
confidence: 99%
“…3,6 Several studies have demonstrated that the excess opioid prescribing, which has fueled the United States opioid epidemic at its origin, continues to be a serious problem, [7][8][9] including within our own profession. [10][11][12][13] My experiences with excess opioid prescribing and opioid misinformation began while on a clerkship in 2014. I was working with the chief resident at an "elite" podiatry residency program.…”
mentioning
confidence: 99%
“…At minimum, please inform your prescribing practice by reading the published articles in the three Opioid Editions of JAPMA to learn more about how your peers treat postoperative pain as well as some helpful tips and tricks. [11][12][13][14][15]…”
mentioning
confidence: 99%